TACI‐dependent APRIL signaling maintains autoreactive B cells in a mouse model of systemic lupus erythematosus. Issue 4 (7th April 2017) - Tran, Ngoc Lan; Schneider, Pascal; Santiago‐Raber, Marie‐Laure
Abstract : APRIL and its receptors TACI and BCMA are key molecules involved in B‐cell differentiation and plasma cell survival. Introduction of APRIL null mutation and generation of TACI‐, BCMA‐, and double TACI.BCMA‐deficiency in lupus‐prone mice revealed the critical implication of TACI‐dependent APRIL signaling in response to T‐independent type II antigens. Abstract : Autoantibodies contribute to the development of systemic lupus erythematosus (SLE). APRIL (a proliferation‐inducing ligand), a member of the TNF superfamily, regulates plasma‐cell survival and binds to TACI (transmembrane activator CAML interactor) and BCMA (B‐cell maturation antigen). We previously showed that APRIL blockade delayed disease onset in lupus‐prone mice. In order to evaluate the role of APRIL receptors in the development of SLE, APRIL, TACI, BCMA, or double TACI.BCMA null mutations were introduced into the Nba2. Yaa (Y‐linked autoimmune acceleration) spontaneous lupus mouse model. Mortality as a consequence of glomerulonephritis (GN) was reduced in Nba2.APRIL −/− . Yaa, Nba2.TACI −/− . Yaa and double‐KO mice compared with Nba2. Yaa mice and correlated with lower levels of circulating antibodies, while splenic populations remained unchanged. In contrast, the appearance of symptoms was accelerated in BCMA‐deficient mice, in which TACI signaling was increased. Finally, lupus‐prone mice deficient for the APRIL‐TACI axis produced less pathogenic antibodies and developed less GN. Disease reduction was attributed to impaired T‐independent type 2 responses when the APRIL‐TACI signaling axis was disrupted. Collectively, our results have identified and confirmed APRIL as a new target involved in B‐cell activation, in the maintenance of plasma cell survival and subsequent increased autoantibody production that sustains lupus development in mice.